Comparative Total and Unbound Pharmacokinetics of Cefazolin Administered by Bolus Versus Continuous Infusion in Patients Undergoing Major Surgery: A Randomized Controlled Trial. Issue 5 (October 2017) - Naik, B. I.; Roger, C.; Ikeda, K.; Todorovic, M. S.; Wallis, S. C.; Lipman, J.; Roberts, J. A.
Abstract : (Abstracted from Br J Anaesth, 118(6):876–882, 2017) Administration of the antibiotic cefazolin before incision can reduce the incidence of surgical site infections, thereby reducing postoperative morbidity rates. Following the initial preincision dose, redosing intervals of cefazolin vary between 2 and 5 hours, depending on patient and procedure variables.